2013
DOI: 10.1212/wnl.0b013e318293e2fe
|View full text |Cite
|
Sign up to set email alerts
|

Urine toxicology screening in an urban stroke and TIA population

Abstract: In this study, patients with stroke and TIA who were young and black were more likely to have urine toxicology screening. Eleven percent of all tested patients (and 9% of patients 50 years or older) were positive for cocaine. To avoid disparities, we suggest that all stroke and TIA patients be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
(15 reference statements)
3
16
1
Order By: Relevance
“…In agreement with the previous study [30], our findings also confirmed that cocaine exposure promotes more ICH, but not ischemic stroke, in AA when compared to non-AA, supporting the claim that the AA ethnicity has a higher incidence of illicit drug-related CVD [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the previous study [30], our findings also confirmed that cocaine exposure promotes more ICH, but not ischemic stroke, in AA when compared to non-AA, supporting the claim that the AA ethnicity has a higher incidence of illicit drug-related CVD [30].…”
Section: Discussionsupporting
confidence: 92%
“…A high risk of stroke occurs shortly after use of cocaine as the onset of stroke symptoms was usually found immediately or within 3 hours after cocaine use [1,11]. Cocaine-induced hemodynamic changes may be related to ICH [29], particularly in active cocaine users [30], with higher risk of aneurysm rupture causing subarachnoid hemorrhage [30], worse functional outcomes and higher mortality when compared to non-cocaine-users [31]. Autopsy studies demonstrated a higher incidence of hypertensive cardiovascular disease in cocaine-induced hemorrhagic stroke [32].…”
Section: Discussionmentioning
confidence: 99%
“…The oldest patient with a positive test was 71 years of age, and 9% of all patients ≥50 years of age tested positive for cocaine. 457 Proposed mechanisms of cocaine-associated ischemic stroke include vasoconstriction, increased platelet aggregation, accelerated atherosclerosis, and vascular cell death resulting in vessel weakening and dissection. The largest available published series on the use of alteplase in cocaineassociated ischemic stroke comprised 29 patients who were compared with 75 alteplase-treated patients with ischemic stroke without drug use.…”
Section: Drug Use (Cocaine)mentioning
confidence: 99%
“…In such cases, direct questioning is of value in all patients, with urine testing of value in some. Unfortunately, in the absence of standardized guidelines for urine testing in the context of suspected cocaine-related cardiovascular events, toxicology screening appears to be performed most frequently in young black males [65], raising concerns regarding issues of health and treatment disparity [66]. The rate of self-report of illicit drug use is just over 50% in patients with a positive toxicology screen upon presentation to the emergency department with chief complaint of chest pain [67], suggesting that urine screening may be a valuable and under-utilized tool.…”
Section: Diagnosismentioning
confidence: 99%